1974
DOI: 10.1111/j.1476-5381.1974.tb09592.x
|View full text |Cite
|
Sign up to set email alerts
|

Modification of Brain Acetylcholine Release by Morphine and Its Antagonists in Normal and Morphine‐dependent Rats

Abstract: The spontaneous release of acetylcholine (ACh) from the cerebral cortex of control and morphine-dependent rats was investigated. The rate of resting output of ACh in morphine-dependent animals was lower than that in the control animals. 2 Administration of naloxone and nalorphine to morphine-dependent rats was followed by a significant rise in the release of cortical ACh. In control rats no such increase in the release of ACh occurred after similar injections of narcotic antagonists. 3 Injections of morphine p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
0

Year Published

1976
1976
1993
1993

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(23 citation statements)
references
References 19 publications
3
20
0
Order By: Relevance
“…The release of cortical ACh was investigated in the presence of neostigmine (50 j±g/ml) and atropine (0.5 gig/ml) using the cup technique of MacIntosh & Oborin (1953). Experimental details of the procedure, as employed in the rat, have been described fully in a previous paper (Jhamandas & Sutak, 1974 …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The release of cortical ACh was investigated in the presence of neostigmine (50 j±g/ml) and atropine (0.5 gig/ml) using the cup technique of MacIntosh & Oborin (1953). Experimental details of the procedure, as employed in the rat, have been described fully in a previous paper (Jhamandas & Sutak, 1974 …”
Section: Methodsmentioning
confidence: 99%
“…Studies reported from this and other laboratories show that the opiate antagonist naloxone, when administered to chronically morphine-treated animals, enhances the output of ACh in the cerebral cortex (Jhamandas & Sutak, 1974;Labrecque & Domino, 1974;Mullins & Phillis, 1974). Morphine itself can inhibit the release of ACh in the CNS and this effect can be antagonized by naloxone administered before or after morphine treatment (Jhamandas, Phillis & Pinsky, 1971; Matthews, Labrecque & Domino, 1973;Yaksh & Yamamura, 1975).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, some reports argue against this view. First, cortical ACh release has repeatedly been found to increase, rather than decrease, during naloxone-precipitated morphine abstinence in the rat (Jhamandas & Sutak, 1974; 'Correspondence. Casamenti et al, 1980;Crossland & Ahmed, 1984).…”
Section: Introductionmentioning
confidence: 99%
“…Morphine-related opiates and enkephalins act on specific opiate receptors to depress the peripheral and central release of acetylcholine (ACh) (Jhamandas & Sutak, 1974;Jhamandas, Hron & Sutak, 1975). The inhibitory actions of morphine on the release of ACh from the guinea-pig ileum or the rat cerebral cortex can be selectively antagonized by the methylxanthines, theophylline (Theo) and caffeine .…”
Section: Introductionmentioning
confidence: 99%